2015
DOI: 10.4103/0972-0707.168800
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the biocompatibility of the Indian Portland cement with potential for use in dentistry: An animal study

Abstract: Aims:This study evaluated the biocompatibility of the Indian Portland cement with potential for use in dentistry.Materials and Methods:This study was performed in Swiss albino mice, by implanting the Indian Portland cement pellets subcutaneously. After 1, 3, and 6 weeks the tissue specimens were prepared for histological examination.Results:The histological analysis showed moderate to severe inflammation at 1 week. The inflammation gradually decreased by 6 weeks, with most of the specimens showing the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…3,8 Mangala et al evaluated the biocompatibility of the Indian Portland cement Birla white in pellet forms. 17 Group II (MTA) and Group IV (WPC + Iodoform) showed similar tissue reactions, and there was no significant difference between them in all experimental periods. The previous study proved that PC + iodoform showed a similar inflammatory reaction when compared to MTA.…”
Section: Discussionmentioning
confidence: 76%
“…3,8 Mangala et al evaluated the biocompatibility of the Indian Portland cement Birla white in pellet forms. 17 Group II (MTA) and Group IV (WPC + Iodoform) showed similar tissue reactions, and there was no significant difference between them in all experimental periods. The previous study proved that PC + iodoform showed a similar inflammatory reaction when compared to MTA.…”
Section: Discussionmentioning
confidence: 76%
“…The biocompatibility evaluation of endodontic sealers, are usually performed in the subcutaneous tissue of rats,[ 4 6 9 18 ] which are limited to histological aspects of tissue reactions induced by the material's components and studies on the expression of extracellular matrix proteins during tissue repair are scarce. In this repair process occurs the participation of two glycoproteins present in the extracellular matrix: Tenascin (TN) and fibronectin (FN).…”
Section: Introductionmentioning
confidence: 99%
“…7 It is a hydrophilic cement that can set in the presence of water. 8 There are several studies that have demonstrated its excellent sealing ability. However, the MTA has certain drawbacks, i.e., presence of toxic elements, difficulty in handling, long setting time, and high material cost.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, the possibility of using Portland cement as a less expensive alternative to MTA in dental practice is to be considered. 8…”
Section: Introductionmentioning
confidence: 99%